2009
DOI: 10.1111/j.1440-172x.2009.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing prioritization of the patient need for care: A tacit knowledge embedded in the clinical decision‐making literature

Abstract: Nursing prioritization of the patient need for care: A tacit knowledge embedded in the clinical decision-making literatureEvery day in clinical settings, nurses practise in complex and dynamic situations. Nurses work to achieve emergent order in these situations through nursing prioritization of the patient need for care. As direct research on nursing prioritization had not been reported, a study, using critical realism as method, was designed to discern the profession's embedded understanding from within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 107 publications
2
48
0
3
Order By: Relevance
“…The prioritization of activities is a basic element in nursing [32], and, in the case of the central services, the person who requests a task does not see how it is carried out. Consequently, the on-demand work undertaken by pharmacy nurses results in enormous pressure, arising, for example, from ward nurses making an urgent request by telephone or by notes on the PRN drug forms; day-hospital nurses urging a cytotoxic treatment to be brought forward; hospital porters requesting the narcotics; pharmacists demanding the immediate preparation of solutions or sterile preparations; outpatients seeking their eye-drops; and preparing inhaled mixtures or parenteral nutrition [33].…”
Section: Discussionmentioning
confidence: 99%
“…The prioritization of activities is a basic element in nursing [32], and, in the case of the central services, the person who requests a task does not see how it is carried out. Consequently, the on-demand work undertaken by pharmacy nurses results in enormous pressure, arising, for example, from ward nurses making an urgent request by telephone or by notes on the PRN drug forms; day-hospital nurses urging a cytotoxic treatment to be brought forward; hospital porters requesting the narcotics; pharmacists demanding the immediate preparation of solutions or sterile preparations; outpatients seeking their eye-drops; and preparing inhaled mixtures or parenteral nutrition [33].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of literature on teaching clinical decision-making has found there tends to be a focus on making a diagnosis, with other aspects such as prioritisation, recognising limits and asking for help often neglected (Lake, 2005). It is therefore unsurprising that evidence capturing the perceptions of junior doctors has found that graduates are least prepared in basic 'doctoring skills', with substandard clinical decision-making a consistent finding (Wall et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…En las unidades de cuidado intensivo (UCI), las características de los pacientes hospitalizados y los equipos de alta tecnología, demandan del profesional de enfermería competencias cognitivas y procedimentales interdisciplinarias específicas para resolver e intervenir adecuadamente asuntos críticos del cuidado [14] . No obstante, ellos no encuentran aplicabilidad a la metodología NIC, NANDA y NOC en el área clínica; 78,57% la utilizan en sus actividades de enseñanza y/ o investigación y sólo 18,18% la emplean en la práctica asistencial [7] .…”
Section: Intervenciones De Enfermería Del Campo Fisiológico Complejo unclassified
“…No obstante, ellos no encuentran aplicabilidad a la metodología NIC, NANDA y NOC en el área clínica; 78,57% la utilizan en sus actividades de enseñanza y/ o investigación y sólo 18,18% la emplean en la práctica asistencial [7] . Al parecer, la sobrecarga de trabajo asociada al alto número de pacientes asignados interfieren en la asunción de roles propios [4] Además, en las funciones asignadas se prioriza la optimización del tiempo y los recursos de acuerdo con las exigencias institucionales, limitando el accionar profesional a la ejecución de intervenciones rutinarias que resuelven necesidades básicas; excluyendo asuntos de mayor complejidad a la hora de definir el plan de atención de Enfermería, [2,4,14,15] . Estas observaciones son similares a las expuestas por los profesionales participantes en este estudio.…”
Section: Intervenciones De Enfermería Del Campo Fisiológico Complejo unclassified